MAGNESIUM DEFICIENCY IN OBSTETRICS AND GYNECOLOGY - C. Dadak (Акушерство, гинекология и репродукция)
Biological role of magnesium in the human body is proved and very well-known. The pathogenesis of obstetrics and gynecology pathology shows that, next to magnesium, pyridoxine plays a key role. An effective strategy for prevention premature delivery, preeclampsia and eclampsia is proved to be timely magnesium sulfate application. We also have facts about its neuroprotective effect on the fetus. However the possibility of overdosage and serious side effects lead to a restricted usage of magnesium sulfate. To minimize the risk of overdosage, its necessary to follow the standard protocols, to make independent crosscheck and to monitor the condition of the patient. Its also reasonable to take magnesium sulfateorally - apart from better bioavailability,overdosage won’t cause serious side effects. Organic magnesium sulfate for magnesium deficiency control and associated symptoms is also justified for premenstrual syndrome (PMS), when COC (Combined Oral Contraceptives) and HRT (hormonal replacement therapy) is prescribed for women undergoing menopause. Magnesium citrate is more preferable because citrate-anion facilitates high bioavailability of magnesium, its also necessary in Krebs cycle and it turns into carbon dioxide and water. Due to this citrate is a perfect transporter of magnesium to the cells.